XM Satellite Radio: Revolutionizing the Airwaves - Homa, Ken (Senate Hall Academic Publishing, 2005)
Based primarily on public information, the XM case was written for an MBA Marketing Strategy course focused on technology adoption. It has also been used with undergraduates and executives, both in “survey” courses and specialized courses on pricing, market forecasting, and promotion. The case broadly covers XM’s marketing challenge: how to capitalize on a $1.5 billion investment to achieve a stated goal of “revolutionizing the airwaves” and becoming “a premier nationwide provider of audio entertainment and information programming”. Market forecasts indicated a potential of almost 50 million subscribers. During its first year, XM spent over $100 on promotion but signed up less than 500,000 subscribers—far below the 4 to 7 million subscribers required to break even. The company was bleeding red ink with a high “burn rate” that had depleted cash reserves. The company had scrounged supplemental financing, but still faced a crisis of market and financial viability.
Keywords: marketing strategy; technology adoption; satellite radio; new products; radio broadcasting; digital music